2021
DOI: 10.1136/bmjopen-2020-044278
|View full text |Cite
|
Sign up to set email alerts
|

Predictive utility of the Activity Measure for Post-Acute Care ‘6-Clicks’ short forms on discharge disposition and effect on readmissions: a retrospective observational cohort study

Abstract: ObjectivesTo evaluate the predictive utility of the Activity Measure for Post-Acute Care ‘6-Clicks’ daily activity and basic mobility functional assessment short forms on inpatient discharge to home compared with skilled nursing facilities, including by diagnostic group (trauma injury, major lower joint replacement/reattachment, spinal fusion excluding cervical), as well as assess the effect of the short forms on 30-day inpatient readmissions.DesignRetrospective, observational cohort study of electronic health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…This procedure yielded contingency tables of predicted and actual frequencies, which were used to calculate sensitivity and specificity and their respective 95% confidence intervals. 10 , 16 , 19 Positive and negative predictive values (PPVs and NPVs, respectively) were also generated from the contingency table values. Hosmer and Lemeshow tests with P >.05 indicated goodness of fit of the logistic regression model.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This procedure yielded contingency tables of predicted and actual frequencies, which were used to calculate sensitivity and specificity and their respective 95% confidence intervals. 10 , 16 , 19 Positive and negative predictive values (PPVs and NPVs, respectively) were also generated from the contingency table values. Hosmer and Lemeshow tests with P >.05 indicated goodness of fit of the logistic regression model.…”
Section: Methodsmentioning
confidence: 99%
“…These tools document degree of difficulty or assistance needed for functional tasks 3 with strong validity, 3 , 4 interrater reliability, 4 , 5 , 6 , 7 and sensitivity to change over time. 8 , 9 Recent research confirmed that the “6-Clicks” tools may play an important role in predicting discharge destination in acute care 6 , 10 , 11 , 12 , 13 , 14 , 15 , 16 and other inpatient 17 , 18 , 19 and outpatient settings. 20 , 21 , 22 , 23 Clinicians may use Basic Mobility and/or the Daily Activities “6-Clicks” scores along with factors such as patients’ personal circumstances in deciding whether discharge to home, with or without services, or an institution (skilled nursing facility [SNF] or inpatient rehabilitation facility [IRF]) best meets patients’ needs.…”
mentioning
confidence: 97%
See 3 more Smart Citations